Foreign Tourism in Brazil: Is the Sky the Limit? - Dixon, Andrew D. (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: The Federal Republic of Brazil is a vast expanse of natural beauty that is just waiting to be discovered by foreign tourists. The country has what foreign tourists want: miles of deserted beaches, unspoiled natural beauty, a vibrant people and culture, and an infectious lightness of heart. Foreign tourism is strong, but has the potential to skyrocket off the charts. Why has this not happened yet? It is a promotional issue in that most foreign tourists have not been informed yet of the splendor that awaits them. Thus, the federal government has initiated a promotional branding campaign with the goal of showing the beauty of Brazil to the world. Such efforts are a good start, but deep challenges exist that must be overcome if the foreign tourism industry is to reach its massive potential. Some of these issues are more societal and others are simply a result of a lack of attention. Nevertheless, the federal government faces a considerable task as it must fight the tourism battle on two fronts. Internationally, it must continue to push ahead with its branding campaign in order for the world to see Brazil in the best possible light. Domestically, it must deal with the various problems faced by the foreign tourism industry. If successful, the future of foreign tourism in Brazil is certain to be bright. In this paper, I attempt to analyze the present state of the foreign tourism industry in Brazil, examine the hurdles that it faces, and then present recommendations for how to improve the industry. I begin with a background description of foreign tourism in Brazil. I then look at the role of tourism in the country's foreign direct investment. I next explain the concept of state branding and describe how the Brazilian government is using branding as a tool to enhance the county's image abroad. Following this, I investigate the difficulties faced by Brazil's foreign tourism industry, and conclude with recommendations for how the government can attract a greater number of foreign tourists.